PEMANFAATAN SMARTPHONE DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Achmad Danial; Muyasaroh Muyasaroh (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2023)
Smartphones are electronic devices whose development is quite rapid in modern times like today, in the world of work smartphones have begun to be used to help with work, while in the world of education smartphones are also used as media and learning resources especially during the Covid-19 pandemic, where learning is carried out online. online, so there is a need for media to support learning, including smartphone media, as was done at Muhammadiyah 4 Kebomas Middle School, where smartphones have been used as learning media for Islamic religious education to date. This type of research is descriptive qualitative, in which the subjects of the study are school principals, PAI teachers, deputy student representatives, parents and student representatives. While the data collection uses three data collection techniques namely observation, interviews, and documentation. The results of this study indicate that online learning using smartphones at SMP Muhammadiyah 4 Kebomas Gresik has several obstacles and is considered less effective because not all students have learning media.